Reverse acculturation among returnees Saudi male students: A hermeneutic phenomenological study - Alqahtani, Ebtesam Mohammed (Journal of International Students, 2026)
This study explores the lived experiences of Saudi male students returning from higher education in Western contexts, primarily the United States, and the challenges encountered during social and cultural reintegration. Guided by hermeneutic phenomenology via van Manen’s interpretative approach, this study examines how reverse acculturation shapes identity, masculinity, and family relationships within the context of Saudi Arabia’s ongoing transformation under Vision 2030. In-depth interviews were conducted with ten Saudi male returnees and analyzed thematically following Braun and Clarke’s framework. Five themes emerged: identity conflict and reverse acculturation stress, renegotiation of masculinity, family disruption and generational tension, barriers to social reintegration, and the navigation of Vision 2030 expectations. The participants reported emotional dissonance, cultural liminality, and tension between traditional norms and egalitarian values acquired abroad. Despite these challenges, many expressed cautious optimism about their ability to contribute to national modernization.